Sick kids in love - Moskowitz, Hannah (Fort Collins, CO : Entangled Teen, an imprint of Entangled Publishing LLC, 2019)
When Isabel, who has rheumatoid arthritis, meets Sasha, a boy with a chronic illness, she considers breaking her no dating rule for him.
Includes readers group guide.
Keywords: Teenagers -- Health -- Fiction; Dating (Social customs) -- Fiction; Love -- Fiction